We-Care-Well: exploring the personal recovery of mental health caregivers through Participatory Action Research - Redublo, Tyler; Paul, Sayani; Joshi, Anahita; Arbour, Simone; Murray, Ross; Chiu, Mary (Frontiers in Public Health, 2024)
Family caregivers play a critical role in supporting the recovery journeys of their loved ones, yet the recovery journeys of family caregivers have not been well-explored. Using a Participatory Action Research approach, we explore the personal recovery journeys of family caregivers for individuals with mental illness. This case study involved piloting and exploring the impact of a novel online workshop series offered to mental health caregivers at Ontario Shores Center for Mental Health Sciences. Recovery courses and workshops conventionally engage patients living with mental health conditions. In the current case, the recovery model is adapted to the needs and experiences of their family caregivers, resulting in a pilot workshop series called “We Care Well”. Through participant-led discussions, interactive and take-home activities, and experiential learning, caregivers co-created workshop content and engaged in peer-learning on seven personal recovery-oriented topics. This included: self-care, resilience-building, non-violent communication, storytelling, and mental health advocacy. Throughout the sessions, participants implemented their learnings into their caregiving roles, and shared their experiences with the group to progress through their own recovery journeys. The We Care Well series was found to be an effective intervention to adapt and apply the personal recovery framework to mental health caregivers. PAR, and co-design are viable approaches to engage caregivers in mental health research, and can facilitate knowledge exchange, as well as relationship building with peers and program facilitators.